Chronic lymphocytic leukaemia – a new revolution in treatment strategies? (Hematology Meeting Reports, 2009)
Chronic lymphocytic leukaemia (CLL) is the most frequently diagnosed type of leukaemia in the Western world. The majority of patients are > 65 years of age at diagnosis and the disease follows an extremely variable clinical course, with overall survival (OS) times ranging from months to decades. Recent advances in molecular biology and immunophenotyping have allowed the stratification of patients into specific risk groups. This could provide the basis for evaluating different treatment options for each group. Dramatic advances in the available treatment options for CLL have occurred alongside improvements in our understanding of the pathobiology of CLL. The introduction of immunotherapy such as rituximab to the treatment armamentarium has transformed the treatment of CLL, improving the outlook for both newly diagnosed and relapsed patients, in terms of extending progression-free survival and probably OS. This review aims to outline the advances that we have made in both the diagnosis and treatment of CLL, and to consider the benefits of these advances from the patient’s perspective.